A study on operation and maintenance of sewerage treatment plant by Indah Water Konsortium (IWK) / Dang Fathihah Ibrahim - Ibrahim, Dang Fathihah (Faculty of Architecture, Planning and Surveying, 2010)
Maintenance and Operation of Sewerage Treatment Plant (STP) is a one of manage and ensure the environmental and pollution under control which it will be conducted by the knowledge party and they know to in charge maintenance work. This will help to prevent the operation system work. The implement of types of STP will enable the age of system used. Good maintenance management it will sure the user have comfort and satisfaction with the services. STP Subang Jaya, Putrajaya, Pulau Duyung which under Indah Water Konsortium Sdn. Bhd. (IWK) has been choose as the case study to know the types used and operation and maintenance system. All the information and data will analyze and a conclusion will be made regarding the efficiency of the operation and maintenance work which have been done. Lastly several recommendations which to resolve and improve the operation and maintenance work have done from the analysis of the interview of the Operation and Maintenance Department/ unit and user of every STP in case study.